Deuterium as a quantitative tracer of enhanced microbial methane production. (1st April 2021) - Ashley, Kilian; Davis, Katherine J.; Martini, Anna; Vinson, David S.; Gerlach, Robin; Fields, Matthew W.; McIntosh, Jennifer
Highlights: Lab stimulation experiments show uptake of H-isotope tracer into microbial CH4 . Addition of algal extracts likely enhanced acetoclastic methanogenesis. Injection of heavy water can quantify the amount of new CH4 generated in coalbeds. Abstract: Microbial production of natural gas in subsurface organic-rich reservoirs ( e.g ., coal, shale, oil) can be enhanced by the introduction of amendments ( e.g ., algal extracts from biofuel production) to stimulate microbial communities to generate "new" methane resources on human timescales, potentially providing a lower carbon energy source. This study tests deuterated water as a tracer to quantify the amount of "new" methane generated and the effectiveness of Microbial Enhancement of Coalbed Methane (MECoM) approaches, as methanogens incorporate hydrogen from formation waters into methane during methanogenesis. Microorganisms (including methanogens), formation water, and coal obtained from the Powder River Basin were used to establish batch reactor stimulation experiments, using algal extracts, in which incremental amounts of deuterated water were added. The greatest amount of methane was produced in the amended coal-associated experiments and there was a consistent uptake of D into microbial methane. The shorter duration (36 days) coal amended experiment had a lower slope (m = 0.31) of δD-CH4 vs. δD-H2 O and a similar offset between δD-H2 O and δD-CH4 (371.2‰) compared to the longer duration (m = 0.44; 114 days; 358.8‰ offset) experiment, both consistent with the stimulation of primarily acetoclastic methanogenesis. The success of our proof-of-concept laboratory experiments confirms that deuterated water can be used as a quantitative tracer of stimulated coal-associated methanogenic activity. We also provide an example of how it can be applied in field-scale MECoM projects. In addition, deuterated water may serve as a useful tracer for other natural or enhanced subsurface microbial activities, such as microbial enhanced oil recovery or bioremediation of organic contaminants.